2020
DOI: 10.1149/1945-7111/ab9cd3
|View full text |Cite
|
Sign up to set email alerts
|

High Stable Supercapacitors Based on Poly(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methanol Nanonet@Nanotube Array by Template-Free Electrochemical Preparation

Abstract: Poly (3,4-ethylenedioxythiophene) and its derivatives provide an excellent platform as electrode materials for supercapacitors due to their superior stability and conductivity. In this study, a poly (2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methanol (PEDOT-MeOH) porous nanonet (PEDOT-MeOH-PNN), PEDOT-MeOH hollow nanotube array (PEDOT-MeOH-HNA) and PEDOT-MeOH-PNN coated PEDOT-MeOH-HNA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The areal energy density of the supercapacitor reaches 18.22 μW h cm –2 at a power density of 0.42 mW cm –2 . Although it can be observed that the energy density slightly decreases with the power density, the areal energy density of 14.0 μW h cm –2 at a high power density of 15.7 mW cm –2 is still substantial, which is higher than that of the electrochemical energy storage devices based on thiophene derivatives and even better than that of some supercapacitors based on thiophene composite materials, including PEDOT-MeOH/SWCNT (5.35 μW h cm –2 ), PEDOT-MeOH-PNN@PEDOT-MeOH-HNA (3.0 μW h cm –2 ), PEDOT-Cl (11.0 μW h cm –2 ), PEDOT/CC (12 μW h cm –2 ), PEDOT:PSS fiber (8.3 μW h cm –2 ), and PEDOT/GO (15.1 μW h cm –2 ) . The detailed information for each compared device can be found in Table S2.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The areal energy density of the supercapacitor reaches 18.22 μW h cm –2 at a power density of 0.42 mW cm –2 . Although it can be observed that the energy density slightly decreases with the power density, the areal energy density of 14.0 μW h cm –2 at a high power density of 15.7 mW cm –2 is still substantial, which is higher than that of the electrochemical energy storage devices based on thiophene derivatives and even better than that of some supercapacitors based on thiophene composite materials, including PEDOT-MeOH/SWCNT (5.35 μW h cm –2 ), PEDOT-MeOH-PNN@PEDOT-MeOH-HNA (3.0 μW h cm –2 ), PEDOT-Cl (11.0 μW h cm –2 ), PEDOT/CC (12 μW h cm –2 ), PEDOT:PSS fiber (8.3 μW h cm –2 ), and PEDOT/GO (15.1 μW h cm –2 ) . The detailed information for each compared device can be found in Table S2.…”
Section: Resultsmentioning
confidence: 87%
“…Among different pseudocapacitance materials, the CP has become a competitive candidate for electrode materials because of its easy large-scale processability, outstanding electrical conductivity, and high specific capacitance. In addition, through the generation and restoration of electronic defects, the charge-electron transfer of CP is also very fast. , Despite these excellent properties, the collapse of the CP structure caused by the volume swelling in the repeated ion doping–dedoping process reduces the cycling stability of CP, which restrains it from being widely used in practical applications. ,, In this context, the synthesis of low-dimensional CPs, such as poly­(3,4-ethylenedioxythiophene) (PEDOT) nanofibers, polyaniline nanofibers, and polypyrrole nanosheets, has emerged as an effective approach to achieve a spectacular capacitance of the electrodes because of a larger electroactive specific surface area and better ion transportation compared with those of bulk form. Furthermore, the aggregation issue of low-dimensional blocks can be resolved by employing the substrate with the framework structure which can facilitate charge transportation and promote the access of electrolytes to the structure units of the CP-based electrodes. For example, CP hybrid electrodes based on framework structures including nickel nanotube arrays and CoO nanowire arrays demonstrate excellent pseudocapacitance and enhanced cycling stability. Nevertheless, the contribution of framework structures to the pseudocapacitance cannot be separately quantified, making the structure–performance relation still vague.…”
Section: Introductionmentioning
confidence: 99%